Financial frictions and the cash flow – external financing sensitivity: evidence from a panel of Pakistani firms - Abdul Rashid; Noshaba Jabeen (Financial Innovation, 2018)
Abstract This paper uses a large panel of Pakistani non-financial firms over the period 2000–2013 to examine the role of financial constraints in establishing the relationship between cash flow and external financing. The results reveal that there exists a negative and significant relationship between external financing and cash flow. The finding of the substitutionary relation between internal funds availability and external financing has been viewed as evidence supporting the pecking order theory of capital structure. Yet, we show that this negative relationship is weak in case of financially constrained firms. We also analyze how credit multiplier affects external financing decisions of financially constrained and unconstrained firms. The results show that for financially unconstrained firms, the negative sensitively of external financing increases with asset tangibility. However, for financially constrained firms, the negative sensitivity of external financing to cash flow either decreases or turns positive as the tangibility of assets increases. This finding implies that financially constrained firms benefit more from investing in tangible assets because such assets not only help relax financial constraints but also having a potential to be a direct source of funds in periods of negative cash flow shocks.